IMAGE QUALITY ENHANCEMENT USING FILTERING METHODS (International journal of artificial intelligence, 2025)
In my research, I explore methods for improving image quality using frequency-domain analysis and the Fourier transform. The study focuses on the application of frequency filtering techniques for noise suppression, distortion reduction, and enhancement of image sharpness. The article examines the operation principles of low-pass, high-pass, and band-pass filters, including Gaussian and Butterworth filters, as well as their implementation using the Discrete Fourier Transform (DFT).Through a series of experiments, I demonstrated how frequency filtering allows selective manipulation of spectral image components, thereby enhancing contrast and fine details. The obtained results indicate the high effectiveness of Fourier-based filtering methods in processing images affected by various types of noise and blurring, confirming their practical importance for medical imaging, satellite observation, and computer vision applications.